Efeito Zeeman anômalo para o átomo de hidrogênio no espaço não comutativo - Santos, Willien Oliveira dos (2012)
We investigate the anomalous Zeeman effect for the hydrogen atom in noncommutative quantum mechanics. By using of the Bopp's shift method the nonrelativistic regime is evaluated and the noncommutative Hamiltonian is determined. By means the first order perturbation theory, the energy correction is calculated for the case of weak external magnetic field. We obtained the orbital and spin Landé factors on noncommutative space. It is shown that the experimental value for the orbital and spin Landé factors put an upper bound on the magnitude of the parameter of noncommutativity of the order of 0 . (8GeV )-2and 0 . (0; 01GeV )-2, respectively. We use the same perturbation calculation for the null external magnetic eld case, showing that some energy shift appears, modifying the ne structure spectrum. Finally, we calculate the Lamb shift and comparing the result with the experimental value from spectroscopy, we got a new bound for the noncommutative parameter, 0 . (3GeV )-2.